HPV genotyping among women treated for high-grade cervical intraepithelial neoplasia with no lesion in the conization specimen. Issue 2 (May 2015) - Rodríguez-Manfredi, Ágata; van Baars, Romy; Quint, Wim G.V.; Sanchez, Ma Jesús; Torné, Aureli; Ordi, Jaume; del Pino, Marta
Abstract: Objective: To evaluate whether specific HPV genotypes or multiple HPV infection are associated with absence of cervical intraepithelial neoplasia (CIN) in the conization specimen. Methods: In a retrospective study, data were reviewed for women treated by conization at a center in Barcelona, Spain, between 2008 and 2011. Women whose pretreatment biopsy showed CIN2/3 with positive p16 staining but had no lesions in the conization specimen were included in the study group if material was sufficient for HPV genotyping. Age-matched control patients who had CIN2/3 in the conization specimen were selected. HPV genotyping was conducted on all histologic specimens. Results: Both groups contained 43 patients. High-risk HPV genotypes were identified in the conization specimens of 14 (33%) women in the study group and of 42 (98%) in the control group ( P  < 0.001). HPV16/HPV18 was detected in the pretreatment biopsy samples of 27 (63%) women in the study group and 25 (58%) in the control group ( P  = 0.413). Multiple HPV infections were detected pretreatment in 8 (19%) women in the study group and 9 (21%) in the control group ( P  = 0.50). Conclusion: No association was found between HPV genotype or multiple HPV infection and absence of lesion in the conization specimen.